Optical Domain Service Interconnect (ODSI) defining mechanisms forenabling on-demand high-speed capacity from the optical domain. - Copley, A. (IEEE Communications magazine)
Signaling and control mechanisms at the electro-optical boundary, such as IP routers, will one day interconnect with the intelligent optical switched network. Creating this open boundary between the electrical and optical domains is the central goal of the Optical Domain Service Interconnect, a coalition of more than 100 companies formed in 2000. ODSI is working to provide an interface to the optical network that can quickly implement and deploy bandwidth on demand. The initiative previously defined a specification for interoperability. Once in use, network elements at the edge of the intelligent optical network can establish optical paths in real time, as demanded by bandwidth demands or needed to support new and innovative high-speed services